IMPLEMENTATION OF INQUIRY LEARNING MODEL TO INCREASE LOGIC THINKING AND LEARNING ACHIEVEMENT - Suwanto Suwanto; Wachidi Wachidi; Turdjai Turdjai (DIADIK, 2017)
The purpose of this study is: 1) To describe the application of inquiry learning model can improve logical thinking of grade V students SDN.03 Gugus I Tanjung Agung Palik Subdistrict, North Bengkulu Regency. 2) To describe the application of inquiry learning model can improve student achievement class V SDN.03 Gugus I Kecamatan Tanjung Agung Palik North Bengkulu District. 3) To describe the application of inquiry learning model effectively improve mathematics learning achievement of grade V students SDN.03 Gugus I Kecamatan Tanjung Agung Palik, North Bengkulu Regency. This research is a classroom action research with the subject of the research is teachers and students of class V A as class of PTK and class V B as experimental class in SDN 03 Tanjung Agung Palik I District of Tanjung Agung Palik, North Bengkulu Regency consist of three cycles. Data collection through observation, assessment and test sheets. Data analysis using averages and ?: test (ti: test). The quasi-experimental population of VA classes is 15 students, consisting of 7 men and 8 female students. And as a class control VB class also consists of 15 students, consisting of 9 male students and 6 female students. The result of the research can be concluded that the application of inquiry learning model can: 1) improve students' logical thinking ability in mathematics lesson in SDN.03 Tanjung Agung Palik, 2) improve student learning outcomes in mathematics subjects at SDN.03 Tanjung Agung Palik, 3) The application of inquiry learning model effectively increase the learning achievement of class V students in SDN.03 Tanjung Agung Palik I District of Tanjung Agung Palik, North Bengkulu Regency, if through the preparation, planning, implementation, observation and reflection in quasi experimental research. Keywords: Inquiry Model, Logical Thinking, Learning Achievement.